Multiple sclerosis a practical manual for hospital and outpatient care - Perez, Carlos A. 1934- (Cambridge University Press, 2021)
Affecting an estimated 2.5 million people worldwide, multiple sclerosis (MS) is the most common neurological cause of debilitation in young adults. Incurable, and with the precise causes still unknown, both diagnosis and management of the condition is complicated. This book summarizes the latest understanding of the causes of the disease, using accessible, bullet-point text to describe key clinical features and diagnostic criteria. Disease-modifying therapies and management of symptoms, including fatigue, tremor and cognitive changes, are covered in detail. With a chapter focusing solely on presentations in the emergency room, the importance of recognizing these neurological emergencies is emphasised, along with indications for admission in MS patients. The impact of MS on women's reproductive health and the increasing recognition of MS in pediatric patients is also explored. An up-to-date and practical approach to the accurate diagnosis and management of MS, this is an invaluable resource for both hospital and outpatient settings.